Pasos Hacia La Salud: a randomized controlled trial of an internet-delivered physical activity intervention for Latinas. Issue 1 (December 2016) - Marcus, Bess; Hartman, Sheri; Larsen, Britta; Pekmezi, Dori; Dunsiger, Shira; Linke, Sarah; Marquez, Becky; Gans, Kim; Bock, Beth; Mendoza-Vasconez, Andrea; Noble, Madison; Rojas, Carlos
Abstract Background Internet access has grown markedly in Latinos during the past decade. However, there have been no Internet-based physical activity interventions designed for Latinos, despite large disparities in lifestyle-related conditions, such as obesity and diabetes, particularly in Latina women. The current study tested the efficacy of a 6-month culturally adapted, individually tailored, Spanish-language Internet-based physical activity intervention. Methods Inactive Latinas (N  = 205) were randomly assigned to the Tailored Physical Activity Internet Intervention or the Wellness Contact Control Internet Group. Participants in both groups received emails on a tapered schedule over 6 months to alert them to new content on the website. The primary outcome was minutes/week of moderate to vigorous physical activity (MVPA) at 6 months as measured by the 7-Day Physical Activity Recall; activity was also measured by accelerometers. Data were collected between 2011 and 2014 and analyzed in 2015 at the University of California, San Diego. Results Increases in minutes/week of MVPA were significantly greater in the Intervention Group compared to the Control Group (mean difference = 50.00, SE = 9.5, p  < 0.01). Increases in objectively measured MVPA were also significantly larger in the Intervention Group (mean differences = 31.0, SE = 10.7, p  < .01). The Intervention Group was also significantly more likely to meet national physical activity guidelines at 6 months (OR = 3.12, 95 % CI 1.46–6.66, p  < .05). Conclusion Findings from the current study suggest that this Internet-delivered individually tailored intervention successfully increased MVPA in Latinas compared to a Wellness Contact Control Internet Group. Trial registration NCT01834287 .